2016
DOI: 10.1038/srep28383
|View full text |Cite
|
Sign up to set email alerts
|

MDCK cells expressing constitutively active Yes-associated protein (YAP) undergo apical extrusion depending on neighboring cell status

Abstract: Cell competition is a cell-cell interaction by which a cell compares its fitness to that of neighboring cells. The cell with the relatively lower fitness level is the “loser” and actively eliminated, while the cell with the relatively higher fitness level is the “winner” and survives. Recent studies have shown that cells with high Yes-associated protein (YAP) activity win cell competitions but the mechanism is unknown. Here, we report the unexpected finding that cells overexpressing constitutively active YAP u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…S2). These results corroborate previously described results for MDCK cells (38) and extend them to PAM keratinocytes and NIH3T3 fibroblasts—that is, mammalian cells expressing activated YAP1 can be losers in cell competitions with normal cells, a finding that stands in contrast to the case in Drosophila .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…S2). These results corroborate previously described results for MDCK cells (38) and extend them to PAM keratinocytes and NIH3T3 fibroblasts—that is, mammalian cells expressing activated YAP1 can be losers in cell competitions with normal cells, a finding that stands in contrast to the case in Drosophila .…”
Section: Resultssupporting
confidence: 92%
“…A context‐dependent switch between losing and winning in cell competitions is not a new observation. We previously reported that MDCK cells overexpressing active YAP1 became losers when cocultured with WT cells in vitro but were winners when cocultured with cells expressing K‐Ras (G12V) or v‐Src (38, 47). The findings we have presented in this manuscript indicate that a major reason for winner‐loser switching may be a difference in the ability of a cell to adhere to the surface of a culture vessel or matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, normal epithelial tissues often exert anti-tumor effects against neighboring cells that acquire oncogenic alterations (Bissell & Radisky, 2001). For instance, oncogenic cells activating an oncogene such as Ras, Src, ErbB2, or YAP are eliminated from the epithelial layer when surrounded by wild-type cells in mammals (Chiba et al, 2016;Hogan et al, 2009;Kajita et al, 2010;Leung & Brugge, 2012). Similarly, oncogenic cells mutant for an evolutionarily conserved apico-basal polarity gene such as scribble (scrib) or discs large (dlg) are eliminated from the Drosophila imaginal epithelium when surrounded by wild-type cells (Brumby & Richardson, 2003;Woods & Bryant, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In mouse fibroblast NIH3T3 cells, cell competition resulting in apoptosis was reportedly dependent on TEAD activity (Mamada, Sato, Ota, & Sasaki, 2015). We subsequently showed that MDCK cells and mouse hepatocytes also undergo YAP-induced competition (Chiba et al, 2016;Miyamura et al, 2017). We generated doxycycline (Dox)-inducible YAP (5SA)-expressing MDCK cells [YAP (5SA) cells] and showed that they succumb to apical extrusion when surrounded by normal MDCK cells.…”
Section: Introductionmentioning
confidence: 99%